Customary Arbitration In Nigeria: A Review Of Extant Judicial Parameters And The Need For Paradigm Shift - Akanbi, Muhammed Mustapha; Abdulrauf, Lukman Adebisi; Daibu, Abdulrazaq Adelodun (Journal of Sustainable Development Law and Policy, 2025)
Two forms of arbitration exist in present-day Nigeria; the first isindigenous to the various communities in the country and it isdetermined by the customs and traditions of the individual community.The second, which was imported, derives its source from the general lawsand practice of England. The latter, which is arguably, alien to the cultureand tradition of traditional Nigerian communities, has often beensuperimposed and applied by courts. The continuing subjugation ofcustomary arbitration can be seen in the attitude of the Nigerian courts,whereby reliance is placed on the parameters of modern arbitration inthe determination of a valid customary arbitration award in Nigeria. Thisarticle contends that the attitudes of courts in the determination of thebinding nature of an award given under customary arbitration, using theparameters of modern arbitration, has caused considerable damage to theessence and potency of customary arbitration practice in Nigeria. In orderto be authentic, it is contended that judicial development of customaryarbitration, must respond to the traditions, attitudes and goals of thepeople whose society is under consideration. It should not be subject toa validity test by reference to orthodox arbitration or arbitration underthe received English law. Consequently, the article examines the extant parameters to which the Nigerian courts subject the characteristics ofcustomary arbitration in Nigeria. The article discusses the need for aparadigm shift in order for customary arbitration to respond to theexigencies of customs.